TARGETING JUSTICE: POPULATION DATA VALIDITY AND GOVERNMENT ASSISTANCE FOR GROCERY STORE BUSINESSES IN NYAMPLUNGAN - Alfiah, Nur; Ghafur, Abdul; Fajri, Ahmad (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
This study analyzes the targeting accuracy of government assistance for grocery store businesses in Nyamplungan Village, Pabean Cantian District, Surabaya, by examining the validity of population data from the perspective of Islamic economics. Using qualitative methods and a case study approach, the data were obtained through interviews with aid recipients and government officials. The findings indicate that some of the population data used remain invalid and do not fully reflect the actual conditions of the recipients. This has implications for inequity in the distribution of assistance, which is inconsistent with the principle of justice ('adl) in Islamic economics. This study emphasizes the need to update and validate data in order to ensure that the assistance mechanism is in line with Sharia principles and contributes to inclusive community welfare.